Educational Ombudsman in Ukraine: Functions, Powers, Activity Directions - Meliakov , Anton; Zub , Alla; Mashkina, Olga (Pressing Problems of Public Administration, 2019)
The article analyzes the prospects of a new position for Ukraine – an educational ombudsman. It is shown that it is an element of a suf ciently extensive system of participants’ rights protection in the educational process. The implementation of the administrative-territorial reform has exacerbated a number of problems that may hinder the rights of the child to education and will obviously be bequeathed to the educational ombudsman. Among these problems are the elimination of schools in rural areas; violation of teachers’ rights to timely and decent pay; bulling; ensuring children with disabilities with the right to education, etc.The ombudsman was supposed to start work from January 1, 2019. These activities are regulated by Article 73 of the Law of Ukraine “On Education”. However, as of April 21, 2019, the individual for the position of the Ombudsman has not been de ned, and the personal composition of his Service, consisting of 15 people, is currently not formed.The authors conducted a survey of teachers of a number of institutions of secondary education in the city of Kharkiv and Kharkiv region. On the basis of the obtained results, it was concluded that teachers are restrained at the initiative of the Cabinet of Ministers on the introduction of this position.In the opinion of about 50% of respondents, the educational ombudsman will become “the next supervisory authority that will distract teachers from their daily work” or “an unimportant position without real in uence and authority”. However, there is also a large (over 45%) share of optimists who expect the ombudsman to become “an effective tool for ensuring the rights of participants in the educational process” in the long run.It is concluded that among the main risks that are expected for this newly created institution are the following. Firstly, duplication of powers, for example, with the Government and the Presidential Commissioners for the Rights of Disabled People, as well as with the relevant departments of the Ministry of Education and Science, the Ministry of Social Policy. Secondly, there is a wide circle of those whose rights he is called to defend, as, in accordance with the current legislation “the educational ombudsman is an of cial who is charged with the tasks of protecting the rights in the  eld of education.” And third, there is lack of regional of ces, which will quickly and negatively affect both the awareness of the ombudsman and the ability of his Service to respond quickly to complaints.